PENERAPAN METODE HYPNOTEACHING DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS PUISI PADA SISWA KELAS X - Sulistiono, hendro (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research was motivated by the difficulties experienced by students in writing poetry texts, the difficulty of students expressing ideas and developing them made the students' learning motivation decreased. Researchers use the hypnoteaching learning method as a solution to assist students in overcoming these difficulties. The purpose of using the hypnoteaching method is expected that students can be more focused, easier to find ideas and increase learning motivation with positive suggestions given by the teacher. This study used an experimental method using the one group pretest-posttest design research. This research used only the same sample. The average score of students using conventional methods got 66.81 and increased after receiving treatment using the hypnoteaching method, the average value obtained by students was 81.39. The difference in the average score of students using conventional methods and hypnoteaching was 14.58. Based on these results it is known that there are differences, namely the results of the average score obtained by students before and after receiving treatment, so the conclusion is that the hypnoteaching method can help students in writing poetry text.